Public Private Partnership: What does the future hold? - Regan, M.; Smith, J.; Love, Peter (RICS, 2009)
Internationally, Public and private Pa11nerships (PPPs) are being used across a wide variety of economic and social infrastructure projects in more than 85 countries. PPPs are a procurement methodology that brings a rigorous risk-weighted approach to major projects using a competitive bid process and private sector expertise and innovation. PPPs are achieving a number of significant improvements in major project procurement and improved public service delivery. This paper considers the prospects of PPPs from the perspective of government clients and their promoters of PPPs and whether current volatility and uncertainty in the capital markets in Australia will affect the feasibility of privately financed infrastructure, and specifically, the PPP method of procurement. A survey of financial advisers and lenders indicates that present market conditions will be placing PPPs under pressure. Future PPPs will be subject to new disciplines - lower leverage, higher reserves, stronger underlying credit credentials, higher debt service coverage criteria and higher cost debt. This will affect both bid depth and state/government risk allocation with lenders expected to take a tougher approach to the support of delivery and operational risks. This suggests some impact on the value for money outcomes for the PPP model in the short-term.